2023
DOI: 10.3389/fcimb.2023.1136674
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on complications of Brucellosis

Abstract: Brucellosis is a common zoonotic disease that is widely spread worldwide and poses a major threat to human health. Clinically, it often presents with non-specific symptoms such as fever, excessive sweating, malaise, myalgia, arthralgia, loss of appetite, weight loss, and enlarged liver, spleen and lymph nodes. The disease has a long and recurrent course, often accumulating in multiple systems and organs. Of these, osteoarticular involvement is the most common complication, with a prevalence of approximately 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…For patients who have not experienced pain relief after rigorous drug therapy, have severe vertebral destruction, and significant compression of the spinal cord and nerves, surgical treatment is necessary ( 18 ). The goal of surgery is to remove the lesions, relieve pain, restore spinal stability, and regain spinal and spinal cord function, ultimately achieving rapid recovery.…”
Section: Discussionmentioning
confidence: 99%
“…For patients who have not experienced pain relief after rigorous drug therapy, have severe vertebral destruction, and significant compression of the spinal cord and nerves, surgical treatment is necessary ( 18 ). The goal of surgery is to remove the lesions, relieve pain, restore spinal stability, and regain spinal and spinal cord function, ultimately achieving rapid recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Its highly elusive and disabling nature makes it a significant concern. Involvement of the central nervous system in brucellosis is relatively rare, accounting for 0.5%–25% of cases ( 2 ). The atypical clinical manifestations of the disease, along with the lack of specific changes in CSF and imaging, contribute to a high prevalence of misdiagnosis and missed diagnosis during the initial stages ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale epidemiological studies have reported complication rates ranging from 27.7 to 90% [ 11 , 14 ]. The main affected anatomical sites were the osteoarticular, hematologic, and genitourinary systems, with incidence ranging from 2 to 77%, 2% to 53%, and 2% to 20%, respectively [ 15 ]. In this study, complications were observed in 54.8% of brucellosis cases, with osteoarticular involvement being the most common, consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%